Ultrasound and echocardiographic findings obtained in the second and third trimesters of gestation in fetuses with normal karyotype and increased nuchal translucency - Hanna Moczulska; Katarzyna Janiak; Maciej Słodki; Maria Respondek-Liberska (Journal of Ultrasonography, 2013)
Introduction: Numerous papers have proven that an increased nuchal translucency is connected with a raised risk of chromosomal aberrations, but few analyses are related to the further state of fetuses with a normal karyotype. The aim of the study was to estimate the risk of cardiac defects and other developmental disorders in fetuses with increased nuchal translucency and normal findings of a standard cytogenetic examination. Methods: The authors carried out a retrospective analysis of 5183 examinations of 3376 patients who reported to the Department of Diagnosis and Prophylaxis of Congenital Malformations in the Polish Mother’s Memorial Hospital in Łódź in the period from January 2008 to March 2011 for prenatal ultrasound and echocardiographic examinations. The authors analyzed the results of the examinations performed in the second and third trimesters of gestation in fetuses with an increased nuchal translucency of ≥3 mm in the first trimester and with a normal karyotype. Results: Fifty-seven patients (1.7% of the examined group) fulfilled the criteria necessary to be included in the study. In 31 pregnant women (54%) structural defects or anomalies of the fetus were found. Cardiac anomalies were detected in 17 fetuses (29.8%). The authors detected various types of cardiac defects such as tetralogy of Fallot, ventricular septal defect, atrioventricular septal defect, transposition of the great arteries and hypoplastic left heart syndrome. Conclusions: In more than half of the fetuses with an increased nuchal translucency (NT≥3 mm) and a normal karyotype, developmental defects of various organs appeared in the further course of pregnancy: mainly heart defects that were either isolated, or accompanied other anomalies.